PENGARUH KOMPETENSI, BEBAN KERJA DAN STRES KERJA TERHADAP WORK ENGAGEMENT DAN IMPLIKASINYA PADA KINERJA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG ACEH - Cut Idawani; Said Musnadi; Mahdani Ibrahim (Jurnal Magister Manajemen, 2018)
The purpose of this research is to know: (1) the influence of the competence to the employee's work engagement (2) the influence of work load on work engagement, (3) the influence of work stress on employee's work engagement (4) the influence of competence to organizational performance (5) on the performance of the organization, (6) the influence of job stress on the performance of the organization (7) the influence of work engagement on the performance (8) the influence of competence, workload and work stress organizational performance through employee work engagement. The object of this research is competence, work load, work stress, employee's work engagement and organizational performance. Data analysis equipment used in research structural equation modeling (SEM) analysis with the help of Amos program. The result of the research shows that the competence, work load, work stress, work engagement and organizational performance, competence influence to work engagement, work load influence to work engagement, work stress influence to work engagement, competence influence to organizational performance, employee also give influence to organizational performance, work stress influence to organizational performance, employee work engagement have positive and significant effect to organizational performance, there is indirect influence of competence, work load and work stress to organizational performance. Because work engagement is partially mediated in mediating competence, workload and job stress on performance, it is advisable to the PUPR leadership if it is to improve the performance of the Dinas it can be done by simply improving the competency, workload and work stress only or also improving the work engagement